Images Enhancement Based on a New Multi-Dimensional Fractal Created by Rectangular Function - Rabab Farhan (Engineering and Technology Journal, 2022)
Digital image processing is a field that is included in many journals due to its importance and the fact that it facilitates the achievement of many scientific and engineering applications worldwide. This specialization is linked with other disciplines, whether medical, engineering, sports, and others, as it facilitates the completion of applications quickly and efficiently. Researchers have discovered and garnered notice as a promising analytic tool in image processing using the idea of fractal dimension. In this effort, a new Multi-Dimensional Fractal (MDF) in view of the rectangle function was introduced a. As an application, the MDF to improve and enhance the images was employed, and found that there is a connection between MDF and image processing, where the self-similarity property, for example, is one of several features in the new definition. Other properties are discussed in the sequel, including image noise reduction. The presence of noise is responsible for properly operating these images in various applications. Several academics have created and applied a strategy for minimizing noise in features multiplicatively throughout the last several years.  The outcomes reveal that the proposed strategy is successful. The method is based on the definition of the rectangular function (the elementary component of all digital signals, videos, and images), where this function indicates a rectangular-formed rhythm that is concentrated at the origin. For example, the suggested process received a rate of 97% for PNSR and 95% for RMSD.